EVALUASI EFEKTIVITAS PENGENDALIAN INTERNAL: STUDI KASUS PADA PT HUTAMA KARYA (PERSERO) - Purana Dewi, Ni Putu Widhi Gita; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2015)
Internal control can improve the accuracy and confidence of accounting information data by preventing errors. There are five components of internal control as a process to produce adequate control. The purpose of this study was to assess the effectiveness of internal control at PT Hutama Karya ( Persero ) Regional Office IV. This research is a quantitative descriptive . The sampling was purposive sampling method , and there are 15 samples. Data collection method used was a questionnaire technique. Based on calculations that are based on respondent's answers regarding internal control PT Hutama Karya ( Persero ) Regional Office IV, which fit into the category quite effective.
Keywords: internal controls , the control environment , risk assessment , control activities , information and communication , monitoring